2016
DOI: 10.3233/jad-160164
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Response to Donepezil in Mild and Moderate Dementia: Relationship to Drug Plasma Concentration and CYP2D6 and APOE Genetic Polymorphisms

Abstract: The clinical response to donepezil in patients with mild and moderate dementia was investigated in relation to the drug plasma concentration and APOE and CYP2D6 polymorphisms. In a prospective naturalistic observational study, 42 patients with Alzheimer's disease (AD) and AD with cerebrovascular disease who took donepezil (10 mg) for 12 months were evaluated. Their DNA was genotyped, and the donepezil plasma concentrations were measured after 3, 6, and 12 months. Good responders scored ≥-1 on the Mini-Mental S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 35 publications
(42 reference statements)
1
27
3
1
Order By: Relevance
“…CYP2D6 and CYP3A4 activities were measured using probe drugs but no direct genotyping was performed. 30 Based on the above conflicting reports, 24,25,27,[29][30][31]33 the current study was selectively conducted in dementia participants with the same degree of disease severity with no other major co-morbidities aiming to substantiate the effects of CYP2D6 genetic variation on drug dose and plasma levels. We demonstrated the relationships between genotypepredicted phenotype with donepezil dose and plasma concentrations in the univariate analysis.…”
mentioning
confidence: 99%
“…CYP2D6 and CYP3A4 activities were measured using probe drugs but no direct genotyping was performed. 30 Based on the above conflicting reports, 24,25,27,[29][30][31]33 the current study was selectively conducted in dementia participants with the same degree of disease severity with no other major co-morbidities aiming to substantiate the effects of CYP2D6 genetic variation on drug dose and plasma levels. We demonstrated the relationships between genotypepredicted phenotype with donepezil dose and plasma concentrations in the univariate analysis.…”
mentioning
confidence: 99%
“…L. Miranda F и соавт. [19] обследовали 42 пациента с БА. Хороший клинический эффект от приема 10 мг донепезила (снижение по шкале MMSE не более чем на 1 балл за 12 мес) коррелировал с более высокой концентрацией препарата в плазме крови, но не с полиморфизмом CYP2D6.…”
Section: Discussionunclassified
“…However, studies investigating this association have shown inconsistent results. [6][7][8][9][10][11][12][13][14] Blood concentration, in turn, might depend on the way the substance is metabolized. Whereas rivastigmine is mainly hydrolyzed and the inactive metabolite renally excreted, 15 donepezil is metabolized by CYP 450 isoenzymes 2D6 and 3A4 in the liver and undergoes glucuronidation.…”
Section: Introductionmentioning
confidence: 99%
“…25 Other factors influencing donepezil or rivastigmine blood concentrations have been described, such as sex, 20 age, [26][27][28] weight, 15,25 daily dose, 26 and duration of treatment. 11 Despite high clinical relevance, only a few studies have investigated the association between CYP2D6 polymorphism, donepezil plasma concentrations, and clinical efficacy of donepezil. While most studies did not find a statistically significant correlation between allele frequency and donepezil concentration or clinical outcome, 10,11,14,29 a few did.…”
Section: Introductionmentioning
confidence: 99%